An Augmented Perceptual-Cognitive Intervention Using a Pattern Recall Paradigm With Junior Soccer Players - Schorer, Jörg; Schapschröer, Marlen; Fischer, Lennart; Habben, Johannes; Baker, Joseph (Frontiers in Psychology, 2018)
In sport, perceptual skill training software is intended to assist tactical training in the field. The aim of this field study was to test whether ‘laboratory-based’ pattern recall training would augment tactical skill training performed on the field. Twenty-six soccer players between 14-16 years of age from a single team participated in this study and were divided into three groups. The first received field training on a specific tactical skill plus cognitive training sessions on the pattern recall task. The second performed only the field training while the third group served as a control group and had field training on other topics. The task on the pre-, post- and retention tests was to recall specific soccer patterns displayed on a computer screen. Results showed significant changes between pre- to post-test performance. There was no significant interaction between groups and tests but the effect size was large. From pre- to retention-test, there was a significant difference between tests and an interaction between groups and tests, but no main effect difference between groups. On the basis of significance testing only retention was affected by the additional training, however, descriptive results and effect sizes from pre- to post-test were as expected and suggested there were learning benefits. Together these results indicate that augmented perceptual-cognitive training might be beneficial, but some limitations in our study design (e.g., missing field test, missing placebo group, etc.) need to be improved in future work.